Study of the Cases of Sexual Assault; Reported at a Tertiary Care Hospital in Bahawalpur (Medical Forum Monthly, 2024)
Objectives: The present study was undertaken with objectives to study the socio-demographic and medico-legal characteristics in victims of sexual assault reporting for medico legal examination at tertiary care hospital at Bahawalpur.Study Design: Observational / descriptive studyPlace and Duration of Study: This study was carried out in the Department of Accident& Emergency of a tertiary care hospital at Bahawalpur from 1st January, 2013 to 31st December, 2014.Materials and Methods: This study was conducted on 87 cases of sexual assault received in the Department of Accident & Emergency of Bahawal Victoria Hospital, Bahawalpur during the calendar years 2013 &2014. The details pertaining to socio-demographic factors such as age, marital status, residential background, and profession of the victim, time interval between the incidence and medico-legal examination and associated physical / genital injuries sustained by the victims were also recorded. The results of the different specimens sent to the forensic science laboratory for further examination were collected & tabulated on a self designed Performa.Results: The study revealed that incidence of sexual assault was common in urban citizens as compared to the rural areas. The most vulnerable age group was 11-20 years involving 36(41.38%) cases followed by those belonging to 3rd decade of life involving 30(34.48%) victims. Of the total 87 cases of alleged sexual assault, 35(40.23%) were students whereas 55 (63.22%) were unmarried. As regard the time interval between sexual assault and examination, 20(22.99%)victims presented themselves for medico legal examinationwithin24 hours of the incidence. Hymen was found torn/ruptured with old tears in 72(82.76%) cases and fresh tear was noticed in 15(17.24%) victims whereas no Virgo intacta was found among all sexual assault cases. Vaginal swabs were found stained with spermatozoa in 56(64.36%) cases and on naked eye examination; the clothes of 22(25.29%)victims were stained with semen.Conclusion: The most vulnerable age group affected by the sexual violence in Bahawalpur belonged to 11-20 years and majority unmarried. Rape &Sexual Assault is underreported crime due to social stigma. A joint effort by law enforcing agencies, Judiciary & civil society should be made in collaboration of electronic and print media to eliminate the sexual violence from the community. The study may help to enhance awareness among public and implement the strategies to make the society a safe place for females particularly the unmarried younger age group.